2023
DOI: 10.1002/sd.2744
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary sustainability reporting assurance in the European Union before the advent of the corporate sustainability reporting directive: The country and firm‐level impact of Sustainable Development Goals

Joanna Krasodomska,
Ewelina Zarzycka,
Paweł Zieniuk

Abstract: Drawing on institutional and signaling theories, this paper investigates country‐and firm‐level impact of Sustainable Development Goals (SDGs) on the European Union (EU) companies' decision to have sustainability reporting assured prior to the implementation of the Corporate Sustainability Reporting Directive (CSRD). The dataset consists of 960 companies based in the EU and covers 2020–2022. The total number of observations equals 2880. The research focuses on SDGs‐related factors influencing companies' assura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(154 reference statements)
0
0
0
Order By: Relevance
“…Auditing firms have adapted their services to provide limited assurance in a variety of fields that are outside the scope of the statutory financial audit [28]. For an EU sample, Krasodomska et al [29] found that larger companies tend to assure their sustainability reports more often, while those operating in environmentally sensitive industries are more reluctant in this regard. The CSRD imposes mandatory limited assurance on sustainability reports, starting with 2024.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditing firms have adapted their services to provide limited assurance in a variety of fields that are outside the scope of the statutory financial audit [28]. For an EU sample, Krasodomska et al [29] found that larger companies tend to assure their sustainability reports more often, while those operating in environmentally sensitive industries are more reluctant in this regard. The CSRD imposes mandatory limited assurance on sustainability reports, starting with 2024.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This will support researchers in synthesizing existing articles and enrich the literature through research results on corporate sustainability and financial performance and the quality of sustainability reporting. We also highlight the need for empirical research activities on corporate sustainability assurance [29], considering the novelty and complexity associated with CSRD requirements, applicable through the European Sustainability Reporting Standards. Therefore, a relevant avenue of future research is analyzing whether corporate sustainability assurance is a positive factor in increasing the quality of corporate disclosures while building investor trust.…”
Section: Future Researchmentioning
confidence: 99%